Association of clinical phenotype and genetic burden in coeliac disease - DOMINGUEZ CASTRO, PATRICIA (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
Coeliac disease (CD) is a chronic small intestinal immune-mediated enteropathy precipitated by exposure to a gluten containing diet in genetically predisposed individuals. The clinical presentation of CD is highly heterogeneous, ranging from severe intestinal symptoms such as diarrhoea and weight loss to subclinical or silent forms of the disease. Many studies have reported a change in the clinical phenotypic presentation of CD in recent years, with an increase in the prevalence of a non-classical and subclinical phenotype at diagnosis as well as the median age of diagnosis. The co-existence of CD with other immune-mediated conditions (IMC) has been well reported in the literature. It is recommended that patients with type 1 diabetes mellitus (T1DM) and autoimmune thyroid disease (ATD) are screened for CD. There is a paucity of data regarding the clinical presentation of CD in the Republic of Ireland (ROI). Genome wide association studies (GWAS) have helped elucidate the polygene architecture of CD, with HLA and non-HLA genes known to contribute to the development of the condition. Little is currently known as to the effects of genotype on clinical phenotype in CD. The use of polygene risk scores (PRS) in CD, combining HLA and non-HLA predisposing loci, have been shown to improve the identification of potential CD patients. However, whilst correlation of PRS with overall disease risk has been well explored, the association of the genotype with CD clinical phenotype has not been extensively investigated. Therefore, studies combining clinical phenotypes with genetic information could potentially explain differences in disease presentation and development. This thesis aimed to provide an updated description of the clinical phenotype of CD in Ireland at present, and to report any potential changes in the presentation of the condition over time. Furthermore, we wanted to explore the ability of PRS to predict differences in disease presentation and prognosis. Our results have corroborated findings reported internationally, that the clinical profile of the disease has changed radically over the past 55 years. Among the changes we found were an increased median age at diagnosis in adulthood, a higher prevalence of non-classical CD at diagnosis, an equal prevalence of patients diagnosed in childhood (<18 years) and patients diagnosed over 65 years and a large percentage of patients presenting either overweight or obese at diagnosis. Also less associated ATD and dermatitis herpetiformis (DH) are observed over time. It seems plausible that these changes are due to improved detection of non-classical disease, and/or potentially shifts in environmental exposures which are engendering changes in the clinical manifestation of CD. Our results also support previous findings that CD patients have an increased occurrence of immune mediated conditions IMCs. Sharing of genetic predisposition loci partially explain the co-existence of CD with other IMCs, however, it is intriguing to see that many of the CD associated IMCs are, like CD itself, increasing their incidence over time. This may indicate that common shared environmental factors have morphed giving rise to greater number of cases of these different conditions. In our study, this hypothesis is supported by the fact that the observed decrease in co-existent ATD is not explained by the age of the patients at data collection or the age of CD diagnosis, but by calendar year of diagnosis. We also found that HLA & non-HLA PRS can predict the age of CD diagnosis in the case of patients with a family history of CD. Moreover, similarly to the case of T1DM, where lower risk genotypes are more prevalent in recent years, our PRS indicate a decreasing genetic burden in CD over the period studied. Notably, HLA-DQ2.5 heterozygotes have latterly become more common in the patient population, which may partly explain the increase in frequency of the disease. Also certain HLA and non-HLA SNPs were identified as significant contributors to this decrease in PRS due to variation in their frequency. The MHC marker rs241420 is of special interest because it shows the largest association with CD, and has been linked to expression of the antiviral gene SKIV2L. Viral infections may be a triggering event in CD, and the association with rs241420 based on existing data, suggests that patients in the later time periods of our study may express less SKIV2L. This observation is interesting given that viral infection is an environmental factor that could therefore be associated with changes in presentation or prevalence. In conclusion, this body of work has reported a changing clinical picture that is linked to a decrease in genetic burden over the duration of our study. This implies that patients are being drawn from a changing genetic pool under the influence of mutating environmental factors.
APPROVED
Keywords: coeliac disease; epidemiology; phenotype; genotype; environmental factors; autoimmunity; gluten; celiac disease